1993
DOI: 10.1042/bst0210244
|View full text |Cite
|
Sign up to set email alerts
|

Properties and intracellular localization of phosphatidylinositol transfer protein in Swiss mouse 3T3 cells

Abstract: In most mammalian cells the endoplasmic reticulum has been identified as the main site of phosphatidylinositol (PI) biosynthesis [ 1, 21. Since the receptor-mediated breakdown of phosphatidylinositol 4,s-bisphosphate (PIP,) and the conversion of PI into PIP, occurs in the plasma membrane [3, 41, the question by what mechanism the level of PI in the plasma membrane is maintained occurs. In a mechanism similar to that proposed for transport of cholesterol [5, 61, it is conceivable that phosphoinositides includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Activation of protein kinase C by phorbol esters affected the cellular localization of the PI-TPs, increasing the association with the Golgi membranes. Both proteins could be phosphorylated in vitro but PI-TPb was phosphorylated to a much higher level than PI-TPa (15,16,32). Actually, it was shown that in vivo 85% of PI-TPb is already phosphorylated on the unique phosphorylation site Ser 262 and that this phosphorylation is essential for the association with the Golgi membranes.…”
Section: Intracellular Localization Of Pi-tpa and Pi-tpbmentioning
confidence: 99%
“…Activation of protein kinase C by phorbol esters affected the cellular localization of the PI-TPs, increasing the association with the Golgi membranes. Both proteins could be phosphorylated in vitro but PI-TPb was phosphorylated to a much higher level than PI-TPa (15,16,32). Actually, it was shown that in vivo 85% of PI-TPb is already phosphorylated on the unique phosphorylation site Ser 262 and that this phosphorylation is essential for the association with the Golgi membranes.…”
Section: Intracellular Localization Of Pi-tpa and Pi-tpbmentioning
confidence: 99%